Pengaruh Sari Kecambah terhadap Karakteristik Kimia Nata De Annona Montana - Ambar Fidyasari; Hurriyatul Ula (PHARMADEMICA : Jurnal Kefarmasian dan Gizi, 2021)
Soursop Mountain (Annona montana Macf.) is a tropical plant that is used as an antioxidant in the form of terpenoid. The mountain soursop fruit that is extracted its juice can be processed into a snack in the form of nata due to its high fibbers content in its fruit. With the addition of Acetobacter xylinum, a layer of cellulose will be formed as a result of fermentation. This study aims to determine the chemical quality of nata de Annona montana with the addition of sprout juice. The data obtained were analysed by the one way ANOVA. This study consists of two stages. First, nata preparation with the addition of sprout juice of 10%, 20%, and 30%. Second, the chemical quality testing which includes the protein content, fat content, water content, ash content and carbohydrate level according to SNI No 01-4317-1996 on the Nata De Coco requirement. The chemical quality testing result on nata de Annona montana shows an increase in its quality with the addition of 30% of sprout juice with a value of 0.8479% of protein content, 1.044% of fat content, 97.53% of moisture content, 13.17% of ash content, and 12.09% of carbohydrate level. In conclusion, the sprout juice has an effect on the chemical characteristics of nata de Annona montana. The best result is obtained at a sprout concentration of 30%.